A prospective observational study on postoperative complications following urological, general surgical, and gynecological procedures in pelvic surgeries. - Baindla, Dr Chandra Prakash; Kanukurthi, Dr. Navyadeep; Sudhakar, Dr. Yerra (Student's Journal of Health Research Africa, 2025)
Background: Pelvic surgeries involving urological, general surgical, and gynecological procedures are highly complex and associated with considerable postoperative morbidity. To evaluate the incidence, spectrum, and predictors of postoperative complications in patients undergoing pelvic surgeries involving urological, general surgical, and gynecological procedures. Methods: This prospective observational study included 100 consecutive patients. Surgical interventions comprised urological procedures (bladder repair, ureteric reimplantation, vesicovaginal fistula repair), general surgical operations (sigmoid volvulus, sigmoid perforation, acute intestinal obstruction, obstructed femoral hernia, pelvic trauma), and gynecological procedures (hysterectomy, ovarian torsion, ectopic pregnancy). Postoperative complications within 30 days were classified using the Clavien–Dindo system, and predictors were analyzed using multivariable logistic regression. Results: The median age was 56 years (IQR: 46–65), with 62% males and 41% ASA class ≥III. Colorectal resection with urological reconstruction was most frequent (54%), followed by cystectomy with diversion (18%), complex fistula repairs (16%), pelvic exenterations (12%), and gynecological surgeries (10%). Open surgery was performed in 58% of cases, while 42% underwent minimally invasive approaches. The median operative time was 310 minutes (IQR: 250–380), with blood loss ≥500 mL in 35%. Overall, 38% developed complications, and 14% had major events (Clavien–Dindo III–V). The most common complications were surgical-site infection (16%), postoperative ileus (14%), and urinary leak (9%). Independent predictors included operative time ≥240 minutes (OR 2.62), blood loss ≥500 mL (OR 3.06), and ASA class ≥III (OR 2.28). Conclusions: Pelvic surgeries involving multidisciplinary teams carry a high incidence of postoperative morbidity. Surgical-site infection, ileus, and urinary leak were the most frequent complications, and prolonged operative time, higher blood loss, and greater ASA class were significant predictors. Recommendations: Preoperative optimization of high-risk patients, multidisciplinary planning, meticulous hemostasis, preference for minimally invasive approaches, and integration of enhanced recovery after surgery protocols are essential to reduce complications and improve outcomes.